Pyrene-containing twistarene : twelve benzene rings fused in a row - Chen, Wangqiao (2020)
Success in obtaining higher-order twistarenes with precise structures is very important for fundamentally understanding the relationship between the structures and physical properties/optoelectronic applications. In this research, by using the advantages from a retro-Diels-Alder process (clean reaction) and the cross-conjugated nature of the pyrene unit, a novel dodeca-twistarene was prepared for the first time. Its structure, confirmed by single-crystal XRD analysis, indicates that it possesses a twisted angle (≈30°), and two neighboring molecules in the crystal lattice are perpendicular to each other because of the twisted character and the strong intermolecular CH-π interactions. However, its basic physicochemical properties suggest its instability in air derives from its elevated HOMO energy level, although NICS calculations confirm that the pyrene units contribution poorly to the π conjugation of the overall molecule.